Prenatal Protein Malnutrition Leads to Hemispheric Differences in the Extracellular Concentrations of Norepinephrine, Dopamine and Serotonin in the Medial Prefrontal Cortex of Adult Rats - Mokler, David J.; McGaughy, Jill A.; Bass, Donna; Morgane, Peter J.; Rosene, Douglas L.; Amaral, Ana C.; Rushmore, R. Jarrett; Galler, Janina R. (Frontiers in Neuroscience, 2019)
Exposure to prenatal protein malnutrition (PPM) leads to a reprogramming of the brain, altering executive functions involving the prefrontal cortex (PFC). In this study we used in vivo microdialysis to assess the effects of PPM on extracellular concentrations of norepinephrine (NE), dopamine (DA) and serotonin (5-HT) bilaterally in the ventral portion of the medial prefrontal cortex (vmPFC) of adult Long-Evans rats. Female Long-Evans rats were fed either a low protein (6%) or normal protein diet (25%) prior to mating and throughout pregnancy. At birth, litters were culled and cross-fostered to dams fed a 25% (adequate) protein diet. At 120 days of age, microdialysis probes were implanted into left and right vmPFC. Basal extracellular concentrations of NE, DA and 5-HT were determined over a one-hour period using HPLC. In rats exposed to PPM there was a decrease in extracellular concentrations of NE and DA in the right vmPFC and an increase in the extracellular concentration of 5-HT in the left vmPFC compared to controls (N = 10 (malnourished), n = 20 well-nourished). Assessment of the laterality of extracellular neurotransmitters in the vmPFC showed that prenatally malnourished animals had a significant shift in laterality for norepinephrine and dopamine to the left hemisphere but a non-significant shift to the left for serotonin. In a related study, these animals and their littermates showed cognitive inflexibility in an attentional task. These data suggest a long-term rewiring of the vmPFC in rats exposed to PPM which may contribute to deficits in attention observed in adult animals exposed to PPM.